2014
DOI: 10.3109/02656736.2014.885590
|View full text |Cite|
|
Sign up to set email alerts
|

Ultrasound-guided percutaneous microwave ablation of solitary T1N0M0 papillary thyroid microcarcinoma: Initial experience

Abstract: During the short-term follow-up period, ultrasound-guided percutaneous MW ablation appears to be a safe and effective technique for solitary T1N0M0 papillary thyroid microcarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
87
7
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(101 citation statements)
references
References 32 publications
6
87
7
1
Order By: Relevance
“…The increased volume of ablation zone at 1 month after RFA was concordant with the results of microwave ablation study for primary PTMC, reported by Yue et al, which must be also due to the ablation of sufficient amount of normal tissue surrounding the thyroid cancer tissue for obtaining the margins free of cancer cells [17]. Complete ablation including the safety margin could result in complete pathologic eradication as shown at the laser ablation study by Valcavi et al [16] and might hinder marginal recurrence after RFA as this study presented.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The increased volume of ablation zone at 1 month after RFA was concordant with the results of microwave ablation study for primary PTMC, reported by Yue et al, which must be also due to the ablation of sufficient amount of normal tissue surrounding the thyroid cancer tissue for obtaining the margins free of cancer cells [17]. Complete ablation including the safety margin could result in complete pathologic eradication as shown at the laser ablation study by Valcavi et al [16] and might hinder marginal recurrence after RFA as this study presented.…”
Section: Discussionsupporting
confidence: 89%
“…A variety of interventional modalities have been successfully applied for treating patients with malignant tumours such as the lung, kidney and liver cancer [10][11][12]. As for thyroid diseases including benign nodules, recurrent and primary cancers, successful application of interventional modalities has been consistently reported [13][14][15][16][17][18][19][20][21][22][23][24]. However, with regard to RFA, reported as a more effective modality among the various interventional modalities in the treatment of benign thyroid nodules [25,26], there were only a few case reports of RFA for primary thyroid cancer [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in laser ablation and microwave ablation, the incidence of nerve injury was 0-8% and 0-4.3%. [20][21][22]27,31 This difference suggests that more security might be expected if BRFA is used in thyroid nodules. Thyroid function tests of BRFA group were normal after treatment in this study.…”
Section: Discussionmentioning
confidence: 94%
“…RF ablation of the head and neck is principally described in the treatment of benign and malignant thyroid nodules, but also in primary and recurrent HNC and in cervical nodal metastasis (11)(12)(13). However, only a few studies have been published regarding the use of MW ablation for HNC (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…RF ablation has been used in head and neck lesions including benign and malignant thyroid nodules (11)(12)(13). However, only a few studies have been published regarding the use of microwave (MW) ablation for head and neck lesions, mostly focused on thyroid lesions (14,15). The purpose of the present study was to describe the novel application of thermal ablation for inoperable head and neck lesions and to evaluate the feasibility, efficacy, and safety of this treatment.…”
mentioning
confidence: 97%